1998
DOI: 10.1139/o98-063
|View full text |Cite
|
Sign up to set email alerts
|

NMR studies of DNA duplexes containing alpha-anomeric nucleotides and polarity reversals

Abstract: We present a summary of our research to date on a family of self-complementary DNA decamers containing single alpha-anomeric nucleotides flanked by 3'-3' and 5'-5' phosphodiester linkages from the perspective of the salient NMR techniques employed to shed light on the structural and dynamic properties of these sequences. Research into this class of synthetic alpha-/beta-oligonucleotides containing mixed strand disposition may have medical relevance given their recently documented efficacy as antisense therapeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Although we have extensively investigated the thermodynamic, enzymatic, and structural properties of DNA duplexes containing localized polarity-reversed α-anomeric residues ( 30 , , a combined thermodynamic and structural study of their effects in physiologically relevant DNA·RNA hybrids has not been reported. With this goal in mind, we embarked on a study of a DNA·RNA nonamer hybrid, d(ATGG-3‘-3‘-αT-5‘-5‘-GCTC)·r(gagcaccau), in which the DNA strand features a central α-anomeric thymidine flanked by polarity-reversing 3‘−3‘ and 5‘−5‘ phosphodiester linkages, along with its unmodified control hybrid and related DNA·DNA and RNA·RNA duplexes (Figure ).…”
mentioning
confidence: 99%
“…Although we have extensively investigated the thermodynamic, enzymatic, and structural properties of DNA duplexes containing localized polarity-reversed α-anomeric residues ( 30 , , a combined thermodynamic and structural study of their effects in physiologically relevant DNA·RNA hybrids has not been reported. With this goal in mind, we embarked on a study of a DNA·RNA nonamer hybrid, d(ATGG-3‘-3‘-αT-5‘-5‘-GCTC)·r(gagcaccau), in which the DNA strand features a central α-anomeric thymidine flanked by polarity-reversing 3‘−3‘ and 5‘−5‘ phosphodiester linkages, along with its unmodified control hybrid and related DNA·DNA and RNA·RNA duplexes (Figure ).…”
mentioning
confidence: 99%